Is the Recently Proposed Mars-Sized Perturber at 65–80 AU Ruled Out by the Cassini Ranging Data? - Iorio, Lorenzo (Frontiers in Astronomy and Space Sciences, 2017)
Recently, the existence of a pointlike pertuber PX with 1 m♂ ≲ mX ≲ 2.4 m⊕ (the symbol “♂” denotes Mars) supposedly moving at 65–80 AU along a moderately inclined orbit has been hypothesized in order to explain certain features of the midplane of the Kuiper Belt Objects (KBOs). We preliminarily selected two possible scenarios for such a PX, and numerically simulated its effect on the Earth-Saturn range ρ(t) by varying some of its orbital parameters over a certain time span; then, we compared our results with some existing actual range residuals. By assuming mX = 1 m♂ and a circular orbit, such a putative new member of our Solar System would nominally perturb ρ(t) by a few km over Δt = 12 year (2004 − 2016). However, the Cassini spacecraft accurately measured ρ(t) to the level of σρ ≃ 100 m. Nonetheless, such a scenario should not be considered as necessarily ruled out since the Cassini data were reduced so far without explicitly modeling any PX. Indeed, a NASA JPL team recently demonstrated that an extra-signature as large as 4 km affecting the Kronian range would be almost completely absorbed in fitting incomplete dynamical models, i.e., without PX itself, to such simulated data, thus not showing up in the standard post-fit range residuals. Larger anomalous signatures would instead occur for mX > 1 m♂. Their nominal amplitude could be as large as 50 − 150 km for mX = 2.4 m⊕, thus making less plausible their existence.